COUNTERPRESSURE FOR DYSMENORRHEA PAIN IN TEENAGERS - Retty Nirmala Santiasari; Siska Christianingsih (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: Teenager is a one of development stages in the life cycle. Female teenagers are often marked by the menstrual phase. Menstruation is often accompanied by pain or what is called dysmenorrhea. Dysmenorrhea is often experienced by female teenagers and it can interfere with the activity and ability of concentration in learning that results in a decrease in performance in school. Counterpressure can be used as a solution to overcome the problem of dysmenorrhea. The counterpressure massage technique is applying strong pressure using the heel of the hand by clenching the lumbar region where there is a uterine sensory nerve that runs with the sympathetic uterus entering the spinal cord through the thoracic nerve 10-11-12 which can increase the endorphin hormone. The purpose of this study was to analyze the effect of counterpressure massage on dysmenorrhea pain in high school students.Objective: The purpose of this study was to analyze the effect of counterpressure massage on dysmenorrhea pain in high school students.Method: The research design used was quasi experiment (one group pre-posttest design). The location of this research was Kartika IV Senior Hight School in Surabaya. The number of respondents was 30 respondents taken by consecutive sampling technique. The instrument was using NRS observation method by Hjermstad (2011). Analysis of the data in this study was using the Wilcoxon Test with a significance level 0.05 with a significance level of 0.05.Result: Wilcoxon test results obtained p value of 0.00 (p <0.05). These results indicate that there are significant differences for dysmenorrhea pain before and after the counterpressure intervention has given.Conclusion: Counterpressure massage techniques can reduce dysmenorrhea pain experienced by female teenagers. Key words: Counterpressure massage, Dysmenorrhea, Female Teenagers.